Effect of humeral stem shape on displacement in elbow implant - Heidari, Milad (2013)
The daily activities are restricted by elbow architecture changes which causes instability and pain. Total elbow arthroplasty is considered last way to relief pain and instability. Various stem cross sectional shapes are designed to reduce loosening of the cemented stemmed implants. The purpose of this study is to analyse the effect of three different humeral stem shapes on implant displacement. Computed tomography scan image was used to reconstruct humerus bone. A three dimensional model of elbow humeral component with three different stem shapes (rectangular, triangular with round edges and circular) with the same length were modelled to be inserted in the constructed bone. All materials were assumed linear, homogenous, elastic and isotropic. A 4 N.m torque was applied and displacement for each implant was analysed. The results of this study showed displacement is more for distal region compared with proximal region. It was also found that rectangular stem had more resistance to torsional loading in comparison with circular and triangular. The present study demonstrates that changing the stem shapes affects the implant displacement and consequently the implant loosening.